Ritual Tabok Sirih Sebagai Upaya Penanganan Keterlambatan Berbicara pada Anak Usia Dini: Magis atau Edukatif? - Saputri, Senny Weyara Dienda; Suroyya, Riza; Yuliati, Nanik (Fakultas Dakwah UIN KHAS Jember, 2024)
This research aims to understand the Tabok Sirih rituals as a treatment for speech delay of young children and the role of the Tabok Sirih rituals in the ecology of early childhood education, especially in handling speech delay problems. The research used descriptive qualitative methods and was carried in Gebang Tengah neighborhood, Gebang village, Patrang district, Jember regency. Data collected from a shaman who performed the Tabok Sirih rituals, 3 preschool children who underwent the rituals and their parents, which start from January until March 2022 using observation and interview methods. Data analysis applied interactive models. As the results, it can be concluded that the Tabok Sirih rituals is a means of educative communication by the shaman to parents so that parents are willing to try to stimulate and train their children's speaking skills continuously. In the ecological system of early childhood education, the Tabok Sirih rituals can act as a mesosystem that bridges the school's need for parental involvement to help stimulate children's language skills.